INFLUENCE OF THE ANODE AND WEHNELT VOLTAGE ON THE CROSSOVER POSITION IN THE ELECTRON BEAM WELDING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Through the numerical modelling methods, the influence of the wehnelt voltage anode voltage on the crossover position of the electron beam welding (EBW) was monitored and analysed. The finite element method (FEM) is used to obtain the simulation results. The formation of the electron beam in the electrostatic part of an electron optic system (EOS) is described by solving the electrostatic task. To obtain the current emitted from cathode, electrical and thermal tasks are solved in the cathode node and Richardson-Dushman equation is used with Schottky correction. By using the results of the electrostatic field, the active emission spot is determined. By simulating the movement of the emitted electrons under the action of the electrostatic field, the shape of the beam is determined and the distance between the cathode and the electrostatic focus is found. The results of the influence of the wehnelt and anode voltage on the magnitude of the emission current and the position of the crossover, as well as the beam dimensions in crossover and anode outlet section at constant cathode heating current are presented.